Fluorescence and photon transmission techniques for studying film formation from PS/GO nanocomposites - M Selin, Sunay; Şaziye, Uğur; Pekcan, Önder (Springer Science and Business Media LLC, 2019)
Steady-state fluorescence and UV–Vis techniques were used to study the film formation behavior of composites consisting of pyrene (P)-labeled polystyrene (PS) latex and graphene oxide (GO) in terms of PS latex/GO volume fraction. PS/GO composite films were prepared on glass substrates with different volume fractions of PS and GO using the drop casting method at room temperature. The film formation behavior of these composites was studied by annealing them at a temperature range of 100–300 °C and monitoring the scattered light intensity (Isc), fluorescence intensity (IP) from P and transmitted light intensity (Itr) through the films after each annealing step. The optical results indicate that PS/GO composites showed complete film formation independent of GO volume fraction. The morphological changes in the films were also found to be in consistent with these results.
Keywords: Graphene; Void closure; MOLECULAR-WEIGHT; SURFACTANT-FREE; Interdiffusion processes; Polystyrene particles; Coalescence; Polymer diffusion; Latex films; ENERGY-TRANSFER